'I Am Who I Am- ': Archetypal drama therapy workshops for Asian American adoptees. Issue 2 (1st October 2019) - Kim, Oh Myo; Ginther, Amy Mihyang
Adopted individuals of colour may experience a number of additional challenges in comparison to non-adoptees due to both pre and post-adoptive stressors. This exploratory study examined four workshops based on drama therapy techniques focusing on archetypal journeys. The majority of participants (N = 24) were Asian American adopted adults between the ages of 24 and 62 years (M age = 34.5 years). In response to an open assessment and Likert scale survey, participants reported that the workshop was both reflective and interesting, although at the same time, it was challenging and sometimes uncomfortable. Participants noted the benefits of using their body and voice, the power of incorporating Korean language and the meaningfulness of having an 'all-adoptee space'.